Visualization, identification, and estimation in the linear panel event study design - Simon Freyaldenhoven; Christian Bailey Hansen; Jorge Pérez Pérez; Jesse M. Shapiro (Banco de México, 2022)
Linear panel models, and the "event-study plots" that often accompany them, are popular tools for learning about policy effects. We discuss the construction of event-study plots and suggest ways to make them more informative. We examine the economic content of different possible identifying assumptions. We explore the performance of the corresponding estimators in simulations, highlighting that a given estimator can perform well or poorly depending on the economic environment. An accompanying Stata package, xtevent, facilitates adoption of our suggestions.
Keywords: C23; C52; 330; Linear Panel Data Models; Difference-in-Differences; Staggered Adoption; Pre-Trends; Event Study